2021
DOI: 10.18510/hssr.2021.947
|View full text |Cite
|
Sign up to set email alerts
|

Concept of Nationalism Employed in the Golden Legend by Nadeem Aslam

Abstract: Purpose of the study: The main purpose of this study is to analyze the novel The Golden Legend by Nadeem Aslam in the light of the concept of Nationalism given by Benedict Anderson in Imagined communities. Methodology: The entire data is evaluated by the entire text related to nationalism. This research is based on qualitative research skills. The basic resource of this research is the novel of Nadeem Aslam, named The Golden Legend. Further, the other resources used in this research are the journals or t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Monaco (2021), in a study, explored the theme of trauma and terror caused by 9/11 in Nadeem Aslam's works as what Shoaib (2020) investigated in his study. Using Nationalism by Benedict Anderson as method of the analysis, Shahzadi et al (2021) explored The Golden Legend and found out that Pakistani people are the symbol of love and peace irrespective of the hardships they have to face during warfare as what Miller (2019) explained in the same fictional work. Sukheeja (2017) also highlighted the theme of both the violence and the hope in the novel in the light of the theories of violence and hope given by prominent scholars like Frantz Fanon, M.K.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Monaco (2021), in a study, explored the theme of trauma and terror caused by 9/11 in Nadeem Aslam's works as what Shoaib (2020) investigated in his study. Using Nationalism by Benedict Anderson as method of the analysis, Shahzadi et al (2021) explored The Golden Legend and found out that Pakistani people are the symbol of love and peace irrespective of the hardships they have to face during warfare as what Miller (2019) explained in the same fictional work. Sukheeja (2017) also highlighted the theme of both the violence and the hope in the novel in the light of the theories of violence and hope given by prominent scholars like Frantz Fanon, M.K.…”
Section: Literature Reviewmentioning
confidence: 99%
“…So far as the role of the circumstances is concerned, the circumstance location (55 times) is on priority as in spite of the hurdles around the characters there is a lot of action, both spatially and the temporally, still to fulfill the hybrid nature of the characters as what Shoaib (2020) fore grounded that in spite of the effects of the drone warfare of 9/11, the marginalized people (women and children) can speak. Miller (2019) and Shahzadi et al (2021) explored the same that Pakistani people are the symbol of love and peace irrespective of the hardships they have to face during warfare. The second number is the circumstance cause (18) foregrounding the reason behind every happening.…”
Section: Findings and Conclusionmentioning
confidence: 99%